Nano-Teaching in Science Education: A Systematic Review of Pedagogical Innovations - Halliru, Abdulkadir; Suwaiba Sa’id Ahmad (Universitas Mandiri, 2025)
This study reported a systematic literature review (SLR) of pedagogical innovations on nano-teaching in science education. Nano-teaching, a streamlined pedagogical approach involving brief teaching episodes (5–10 minutes) followed by immediate feedback, has emerged as a transformative strategy in science education. This systematic review synthesizes 53 peer-reviewed studies from 2014 to 2024 to explore the applications of nano-teaching, impacts, and challenges. Findings of the literature review highlighted its efficacy in enhancing teacher preparation, student engagement, and conceptual understanding of complex scientific concepts. The review includes a comparison of nano-teaching and microteaching, delineates teacher and student roles and provides both a general textual model and a specific sequence for implementing nano-teaching in cyber classrooms. Challenges such as time constraints, scalability, and teacher resistance are addressed, with recommendations for curriculum integration, professional development, and technology-enhanced delivery. This comprehensive analysis underscores nano-teaching’s potential to revolutionize science education while identifying avenues for future research.